An Innovative Approach to Modeling and Sustainable Conservation of Architectural Heritage in Historic Buildings - Haval, Abhijeet Madhukar; Mishra, Nidhi (AIS - Architecture Image Studies, 2025)
Sustainable growth has emerged a goal for all countires striving to achieve equilibrium among ecological, social, and financial needs. The primary aim of a sustainable built environment is to generate innovative models that optimize power and material usage. This concept must contemplate old buildings made years ago. Despite the structural stability of many of these structures, they are outdated, and their potential is not entirely realized. To revitalize and create sustainable value from this structure, adaptive recycling is used to renovate, adapt, and repurpose outmoded buildings to prolong their life cycle while serving a new function. The adaptive redevelopment of a historic structure must exert minimum influence on the heritage value of the structure and its surroundings. A plan of inquiry is formulated to achieve four goals. Initially, literature about sustainable growth, ethical principles, adaptive recycling, and emerging countries is examined; two scenarios are provided and assessed to explore the contribution of adaptive recycling to enhancing the long-term value of heritage structures; thirdly, an approach accompanied by an action model is formulated to promote the adaptable recycle of antique structures in emerging nations; ultimately, study findings are delineated, and suggestions beneficial to professionals engaged in the flexible reuse of significant structures are suggested.